2013
DOI: 10.1037/a0030803
|View full text |Cite
|
Sign up to set email alerts
|

Family-supportive work environments and psychological strain: A longitudinal test of two theories.

Abstract: Based on the Job Demands-Resources (JDR) model (E. Demerouti, A. B. Bakker, F. Nachreiner, & W. B. Schaufeli, 2001, The job demands-resources model of burnout. Journal of Applied Psychology, 86, 499-512) and Conservation of Resources (COR) theory (S. E. Hobfoll, 2002, Social and psychological resources and adaptation. Review of General Psychology, 6, 307-324), we tested three competing models that predict different directions of causation for relationships over time between family-supportive work environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 55 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…It is important to note though that the occurrence of work-to-family conflict has consistently been linked to such diverse well-being outcomes as mood (Williams & Alliger, 1994;Wood, Michaelides, & Totterdell, 2013), domain and life satisfaction (see Allen et al, 2000), depression (Aycan & Eskin, 2005;Frone et al, 1992), physical health (Adams & Jex, 1999;Allen et al, 2000;Frone, Russell, & Barnes, 1996), and affective strain (Lapierre & Allen, 2006; Downloaded by [New York University] at 20:18 05 July 2015 Moreno-Jiménez et al, 2009;Odle-Dusseau et al, 2013). However, these studies capture only pieces of well-being.…”
Section: Mediated Modelmentioning
confidence: 95%
“…It is important to note though that the occurrence of work-to-family conflict has consistently been linked to such diverse well-being outcomes as mood (Williams & Alliger, 1994;Wood, Michaelides, & Totterdell, 2013), domain and life satisfaction (see Allen et al, 2000), depression (Aycan & Eskin, 2005;Frone et al, 1992), physical health (Adams & Jex, 1999;Allen et al, 2000;Frone, Russell, & Barnes, 1996), and affective strain (Lapierre & Allen, 2006; Downloaded by [New York University] at 20:18 05 July 2015 Moreno-Jiménez et al, 2009;Odle-Dusseau et al, 2013). However, these studies capture only pieces of well-being.…”
Section: Mediated Modelmentioning
confidence: 95%
“…In addition, we assessed the opposite causal direction of mental health symptoms predicting changes in impediments from T1–T2 and T2–T3. This approach toward assessing predictors of change has been recommended by prior researchers (Odle‐Dusseau et al., ; Zapf et al., ). In the analyses, perceived stigma, practical barriers, and negative attitudes were used to index the latent variable of impediments at each period, and PTSD and depression symptoms were used to index the latent variable of mental health symptoms at each period.…”
Section: Methodsmentioning
confidence: 99%
“…; Lidwall, Marklund and Voss ; Odle‐Dusseau et al. ). More recently, a large study of 27 European countries observed that poor work–life balance was associated with a significant increase in the risk of poor self‐reported health and well‐being (Lunau et al.…”
Section: Literature Reviewmentioning
confidence: 99%